Effect of Incorporation of De-Oiled Distillers Dried Grain with Solubles in the Concentrate Mixture on Growth Performance of Murrah Buffalo Calves - Pujitha, Tanguturi; Kumar, Mula Ravi; Kavitha, Pathakamuri; Venkata Seshaiah, Chappidi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This experiment was aimed to assess the impact of inclusion of de-oiled DDGS (dDDGS) as source of protein to replace cotton seed  cake protein (CSC) in the concentrate mixture on growth, nutrient digestibility and cost economics. In a 90 days growth trial, 18 buffalo  calves in the age range of 6-9 months old and 79-84 kg BW were randomly divided into three groups and allotted to one of the dietary  treatments. In the experimental feeds CSC (on CP basis) was substituted with de-oiled DDGS at 0% (T1), 50% (T2) and 100% (T3) levels. The  findings suggested that BW, ADG and FCR had significantly (p
Keywords: Buffalo calves; Cost economics; Cottonseed cake; De-oiled DDGS; Digestibility; Growth